2012
DOI: 10.2214/ajr.12.8581
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ and Midlevel Providers’ Awareness of Lifetime Radiation–Attributable Cancer Risk Associated With Commonly Performed CT Studies: Relationship to Practice Behavior

Abstract: Objectives The purpose of this study is to investigate emergency department (ED) providers’ knowledge of the life-time cancer risk attributable to radiation (LAR) from commonly performed CT scans and its association with the ordering providers’ risk/benefit analysis prior to ordering the exam. It further explores factors that may influence provider selection of a particular diagnostic imaging study in an ED setting. Materials and Methods Sixty-seven ED providers at the University of Rochester Medical Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 21 publications
0
34
0
1
Order By: Relevance
“…[5,6] In the ED setting, providers may tend to overutilise CT scans. [2,7] Other factors contributing to CT over-utilisation may include fear of a missed or incorrect diagnosis, the potential for malpractice lawsuits, as well as inadequate knowledge and awareness of radiation exposure and potential risk of inducing cancer. [7] There is an abundance of studies evaluating trends in CT scan use in EDs, with growing pressure to measure and reduce unnecessary imaging in that environment.…”
Section: Researchmentioning
confidence: 99%
“…[5,6] In the ED setting, providers may tend to overutilise CT scans. [2,7] Other factors contributing to CT over-utilisation may include fear of a missed or incorrect diagnosis, the potential for malpractice lawsuits, as well as inadequate knowledge and awareness of radiation exposure and potential risk of inducing cancer. [7] There is an abundance of studies evaluating trends in CT scan use in EDs, with growing pressure to measure and reduce unnecessary imaging in that environment.…”
Section: Researchmentioning
confidence: 99%
“…A total of 12 studies evaluated the understanding of radiation and cancer risk among patients and physicians [12][13][14][15][16][17][18][19][20][21][22][23] (Table 1). …”
Section: Radiation Risk Awareness Among Patients and Providersmentioning
confidence: 99%
“…Five studies further evaluated this awareness by giving stratified probabilities of the estimated lifetime risk of cancer for a CT examination [14,16,17,20,21]. In one study, only the correct estimation was reported and this was used for data analysis [12].…”
Section: Radiation Risk Awareness Among Patients and Providersmentioning
confidence: 99%
“…Medical radiologists themselves underestimate the radiation doses associated with a CT scan by 50-500 times [14] use ionizing radiation [15]. Such faulty knowledge is transferred directly onto patients when they discuss the reasons for having a medical imaging test and its related risks with medical specialists [16][17][18][19][20]. Nonetheless, no one knows the real level of awareness and perception of the risk arising from ionizing radiation in patients receiving diagnostic radiological procedures.…”
Section: Introductionmentioning
confidence: 99%